2010
DOI: 10.2174/157340110790909545
|View full text |Cite
|
Sign up to set email alerts
|

Methods for Assessing Aspects of Carotenoid Bioavailability

Abstract: Carotenoids are a group of C-40 isoprenoid-based molecules with >600 representatives in nature, of which approximately 30 are of importance within our daily diet. This class of phytochemicals has recently attracted much attention due to potential health beneficial effects associated with carotenoid consumption, including reduction of cardiovascular diseases, protection from age-related macular degeneration, various types of cancer, and perhaps, bone health. Therefore, an increasing number of studies have been … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
37
0
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(38 citation statements)
references
References 304 publications
(479 reference statements)
0
37
0
1
Order By: Relevance
“…β-Carotene dispersions were then prepared with compositions as described in Table 1. The prepared dispersions were directly transferred to a clean amber bottle and incubated for 120 min at 37°C with shaking at 95 rpm in an incubator shaker (Biehler & Bohn, 2010). Samples were extracted at given time (0, 5, 40, 80, 120 min) for further tests.…”
Section: In Vitro Release Studiesmentioning
confidence: 99%
“…β-Carotene dispersions were then prepared with compositions as described in Table 1. The prepared dispersions were directly transferred to a clean amber bottle and incubated for 120 min at 37°C with shaking at 95 rpm in an incubator shaker (Biehler & Bohn, 2010). Samples were extracted at given time (0, 5, 40, 80, 120 min) for further tests.…”
Section: In Vitro Release Studiesmentioning
confidence: 99%
“…Furthermore, it has been demonstrated that the evaluation of bioaccessibility by in vitro models can be well correlated with results from human studies and animal models (reviewed by Biehler & Bohn, 2010). Based on an in vitro study, it has been demonstrated that the digestion process decreased the phenolic content by at least 47% in digested fruit beverages compared to undigested ones (Cilla et al, 2009).…”
Section: Introductionmentioning
confidence: 97%
“…Despite their limitations, such as typically constituting only a static model of digestion, in vitro GI models have been developed for bioaccessibility assessment, allowing the study of changes in dietary components during the gastric and the intestinal stage, due to factors impacting their availability discussed above (Biehler & Bohn, 2010;Cilla, González-Sarrías, Tomás-Barberán, Espín, & Barberá, 2009;McDougall et al, 2005). Furthermore, it has been demonstrated that the evaluation of bioaccessibility by in vitro models can be well correlated with results from human studies and animal models (reviewed by Biehler & Bohn, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Those assays are described as being easy, cheap and reproducible, being possible to evaluate the digestive stability of the food constituents (Failla & Chitchumroonchokchai, 2005;Rodríguez-Roque et al, 2013). Furthermore, in some cases, the use of in vitro models to study the bioaccessibility of food constituents have proven to be well correlated with results from human studies and animal models (Biehler & Bohn, 2010;Bouayed et al, 2011).…”
Section: Introductionmentioning
confidence: 99%